Implementasi Program Kampus Mengajar dalam Meningkatkan Kemampuan Literasi Siswa di SDN 027977 Binjai Barat - Hamidah D; Lendra Fachrurrowzi; Dody Salden Chandra; Asmawati Asmawati (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The Teaching Campus Program through the Independent Learning Campus (MBKM) policy is a strategic step for the Ministry of Education and Culture in improving the literacy and numeracy competencies of students in Indonesia. Involving students directly makes a significant contribution in strengthening learning at the elementary school level, according to the needs and conditions the school is facing. With this activity, it is hoped that teachers can be motivated to create a more enjoyable learning atmosphere, especially students who are motivated to continue learning and develop their potential. The School Literacy Movement (GLS) is one of the names of the activities we provide to study literacy in children to increase interest in reading. Increasing students' literacy competency is a positive result of the implementation of the Class 6 Teaching Campus Program at SDN 027977 West Binjai. Hopefully this program will continue to provide positive benefits for education at the school, especially in grades II, IV, V and VI.